Tuberculosis treatment outcomes and associated factors: A retrospective study in West Nusa Tenggara, Indonesia - Meiyanti, Meiyanti; Bachtiar, Adang; Kusumaratna, Rina K.; Alfiyyah, Arifah; Machrumnizar, Machrumnizar; Pusparini, Pusparini (Narra J, 2024)
Successfully treating tuberculosis (TB) could significantly help reduce its spread. The aim of this study was to identify factors associated with successful TB treatment. A retrospective study was conducted in West Nusa Tenggara, Indonesia, using data from the National TB Information System (SITB) covering patients from January 1 to December 31, 2022. Patients were classified into two groups: those with successful treatment outcomes (cured or completed treatment) and those with unsuccessful outcomes (including treatment failure, loss to follow-up, or death). Univariate and multivariate logistic regression analyses were performed to identify factors associated with treatment outcomes, providing odds ratios (OR) and adjusted odds ratios (aOR) with 95% confidence intervals (CIs). A total of 2,225 TB patients (1,382 males and 843 females) were included in the study. Of these, 2,048 (92.1%) achieved successful treatment outcomes. Univariate analysis indicated that older age (OR: 0.47; 95%CI: 0.28–0.78) and a high number of AFB in sputum smears (OR: 0.23; 95%CI: 0.09–0.66) were associated with a higher likelihood of unsuccessful TB treatment. In contrast, having no HIV infection (OR: 13.44; 95%CI: 6.22–29.08), clinical TB cases (diagnosed clinically rather than bacteriologically) (OR: 1.50; 95%CI: 1.04–2.20) and longer duration of TB treatments were associated with successful treatment outcomes. Multivariate analysis suggested that the TB treatment durations of 4–6 months (aOR: 1256.95; 95%CI: 431.89–3658.19) and 7–12 months (aOR: 575.5; 95%CI: 99.1–3342.06) were associated with a significantly higher likelihood of success compared to durations of 0–3 months. In conclusion, this study highlights that a minimum treatment duration of three months was crucial for increasing the likelihood of successful TB treatment. These findings emphasize the importance of comprehensive support programs to ensure adherence to treatment guidelines and improve outcomes.